The changing ethos of the university: living with supercomplexity - Petro van Niekerk (Acta Academica, 2016)
The rationale for the article was to problematise the dominant market ethos and corporate bureaucratic organisation practices prevalent in universities throughout the world and currently the cause of great concern among many South African academics. In response to this phenomenon, theoretical research via a literature study was undertaken to explore new modes of thinking through the lens of Barnett’s concept of supercomplexity. The study highlighted the importance of new coping strategies to deal with complex issues in a constructive way. By accepting that conditions of   supercomplexity cannot be managed in an atomistic and mechanical way and should rather be done by flexible and continual mapping of existing challenges and by foregrounding multiple contestability, I argue that the university during times of supercomplexity should focus on interrelationships between different sectors of the university to re-establish mutual trust relationships. I plead for an appropriate sense of slowness and a focus on the academic core to enable the institution to function more reflectively and appropriately within an age of supercomplexity.